Fabrication and drag reduction of superhydrophobic surface on steel substrates - Zhang, Haifeng; Tuo, Yanjing; Wang, Qingchun; Jin, Bingjie; Yin, Liang; Liu, Xiaowei (Surface engineering, 2018)
Superhydrophobic surfaces have attracted significant attention because of their potential applications in various industrial fields. In this study, a chemical process for fabricating ZnO nanowires on steel substrates is developed by using a chemical etching and hydrothermal synthesis method. The resultant surface exhibits binary micro/nanostructures. The modified sample exhibits a water contact angle of 164.9° and a sliding angle of 2.3° for a 5-μL water droplet. An experimental setup is created to measure the drag friction on the surface of the sample. Experimental results show that the drag reduction radio for the as-prepared sample is 40-50%.